2010
DOI: 10.1002/bip.21422
|View full text |Cite
|
Sign up to set email alerts
|

Circular proteins and mechanisms of cyclization

Abstract: Cyclization via head‐to‐tail linkage of the termini of a peptide chain occurs in only a small percentage of proteins, but engenders the resultant cyclic proteins with exceptional stability. The mechanisms involved are poorly understood and this review attempts to summarize what is known of the events that lead to cyclization. Cyclic proteins are found in both prokaryotic and eukaryotic species. The prokaryotic circular proteins include the bacteriocins and pilins. The eukaryotic circular proteins in mammals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 69 publications
1
85
0
Order By: Relevance
“…Although several of the circular bacteriocins have now been genetically characterized, the enzymes responsible for the different steps of maturation and the mechanisms and potential coupling of the processes are still unknown (6).…”
mentioning
confidence: 99%
“…Although several of the circular bacteriocins have now been genetically characterized, the enzymes responsible for the different steps of maturation and the mechanisms and potential coupling of the processes are still unknown (6).…”
mentioning
confidence: 99%
“…Genes encoding cyclotide precursors from O. affinis, the most studied cyclotide-bearing plant (6), encode proteins that have a conserved motif that flanks the upstream and down-stream processing sites of each cyclotide domain (14). A recent analysis of a large number of cyclotide precursor sequences showed that similar motifs are present in other plant species (15).…”
mentioning
confidence: 99%
“…The conserved motifs that flank the cyclotide domains of the precursor proteins have been proposed to have a crucial role in the cyclization reaction ( Fig. 1C) (14,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the family of antimicrobial peptides, a group characterized by the head-to-tail circularization of their backbone, such as circular bacteriocins, has attracted more attention than their linear counterparts due to their superior structural stability [7,8]. They have huge application potential as safe food preservatives because of their exceptional stability and broad antimicrobial spectra [9].…”
Section: Introductionmentioning
confidence: 99%